Insights on hair, skin and eye color of ancient and contemporary Native Americans - Carratto, Thássia Mayra Telles; Marcorin, Letícia; Debortoli, Guilherme; Hünemeier, Tábita; Norton, Heather; Parra, Esteban Juan; Castelli, Erick C. [UNESP]; Mendes-Junior, Celso Teixeira (Elsevier, 2020)
Over the past few years, tools capable of predicting pigmentation phenotypes have been developed aiming to contribute for criminal and anthropological investigations. In this study, we used eight genetic systems to infer eye, hair, and skin color of ancient and contemporary Native Americans. To achieve this goal, we retrieved 61 SNPs from 42 samples available in free online repositories of DNA sequences. We performed pigmentation predictions using two freely available tools, HIrisPlex-S and Snipper, in addition to two other published models. This workflow made possible to predict all three phenotypes with at least one tool for 29 out of the 42 samples. Considering these 29 individuals, predictions for eye, hair, and skin color were obtained with HIrisPlex-S for 27, 28 and 27 individuals, respectively, while 24, 25 and 25 individuals had such predictions with Snipper. In general, ancient and contemporary Native Americans were predicted to have intermediate/brown eyes, black hair, and intermediate/darker skin pigmentation.
Keywords: Ancient Native Americans; HIrisPlex; HIrisPlex-S; IrisPlex; Snipper